Coping with Adversity Regional Economic Resilience and Public Policy - Wolman, Harold (Cornell University Press, 2017)
Coping with Adversity addresses the question of why some metropolitan-area regional economies are resilient in the face of economic shocks and chronic distress while others are not. It is particularly concerned with what public policies make a difference in whether a region is resilient. The authors employ a wide range of techniques to examine the experience of all metropolitan area economies from 1978-2014. They then look closely at six American metropolitan areas to determine what strategies were employed, which of these contributed to regional economic resilience, and which did not. Charlotte, North Carolina, Seattle, Washington, and Grand Forks, North Dakota, are cases of economic resilience, while Cleveland, Ohio, Hartford, Connecticut, and Detroit, Michigan, are cases of economic nonresilience. The six case studies include hard data on employment, production, and demographics, as well as material on public policies and actions. The authors conclude that there is little that can done in the short term to counter economic shocks; most regions simply rebound naturally after a relatively short period of time. However, they do find that many regions have successfully emerged from periods of prolonged economic distress and that there are policies that can be applied to help them do so. Coping with Adversity will be important reading for all those concerned with local and regional economic development, including public officials, urban planners, and economic developers
Description based on online resource; title from PDF title page (publisher's Web site, viewed 30. Aug 2021)
Keywords: Business (General); Political Science & Political History; Urban Studies; SOCIAL SCIENCE / Sociology / Urban; Financial crises -- United States; Urban policy -- United States